Analysis of the Pelletability of Vegetable Crop Foliage Using a Commercial Flat Die Pellet Mill - Gholami Banadkoki, Omid; Sokhansanj, Shahab; Lau, Anthony (Energies (Basel), 2025)
Agricultural residues serve as a vast yet underutilized biomass resource with significant potential for bioenergy and biomaterial applications. Converting these residues into densified biomass pellets enhances energy density, handling efficiency, and transportability, offering a sustainable alternative to conventional feedstocks. While extensive research has focused on woody biomass, studies on the pelletization of vegetable crop foliage remain limited. This study examines the pelletability of foliage from corn, soybean, tomato, eggplant, cucumber, and summer squash, assessing their physical properties, bulk durability, bulk density, and energy consumption during pelletization. Results demonstrated that variation in biomass composition significantly influences pellet quality, with lignin content improving durability and ash content affecting moisture uptake and combustion properties. Cucumber had the highest pellet density (691.2 kg/m3) and durability (97.9%), making it suitable for long-term storage and transport. Sawdust exhibited the lowest moisture absorption (16–18% db), which is attributed to its highest lignin content. Pelletization energy requirements varied significantly, with cucumber (21.8 kWh/t) and summer squash (18.7 kWh/t) requiring the lowest energy input, whereas soybean (49.6 kWh/t) and sawdust (47.3 kWh/t) exhibited the highest energy demands due to greater resistance to densification. A predictive model was developed to correlate single pellet density and durability with bulk pellet properties—yielding high predictive accuracy, with R2 = 0.936 for bulk density (BDe) and R2 = 0.861 for bulk durability (BDu)—thereby facilitating process optimization for large-scale pellet production. This study demonstrated that foliage residues from greenhouse crops, such as cucumber and summer squash, can be effectively pelletized with low energy input and high physical integrity. These outcomes suggest that such underutilized agricultural residues hold promise as a densified intermediate feedstock, supporting future applications in bioenergy systems and advancing circular resource use in controlled-environment agriculture.